The effect of regional original income and balance funding on regional government financial performance - Noor Farieda Awwaliyah; Ratno Agriyanto; Dessy Noor Farida (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - The purpose of the research was to determine the effect of local revenue and intergovernmental revenue on the financial performance of local government.Method - This research used Stewardship Theory. The method used is quantitative research method. The method of data analysis used is multiple linear regression analysis. This research used secondary data. The population in this research is the Regency in Central Java which consists of 29 regencies and 6 cities.Result - The results showed that first, local revenue had positive effect on financial performance of local government. Second, intergovernmental revenue had positive effect on financial performance of local government. Third, local revenue and intergovernmental revenue together had influence on financial performance of local government.Implication - The practical implication of this research is that the Regency Governments in Central Java  are expected to reduce dependence on the central government by optimizing the potential of existing income sources to be able to further improve their financial performance.Originality - An originality of research is focused on two  variables; regional original income and intergovernmental revenue and uses the measurement of independence index for the dependent variable. financing.